hBMSC-Derived Extracellular Vesicles Attenuate IL-1β-Induced Catabolic Effects on OA-Chondrocytes by Regulating Pro-inflammatory Signaling Pathways - Li, Shushan; Stöckl, Sabine; Lukas, Christoph; Götz, Julia; Herrmann, Marietta; Federlin, Marianne; Grässel, Susanne (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Human bone marrow derived mesenchymal stromal cells (hBMSCs) provide a promising therapeutic approach in the cell-based therapy of osteoarthritis (OA). Several disadvantages evolved making it necessary to search for alternative treatment options. Extracellular vesicles (EVs) are released by multiple cell types into the extracellular microenvironment, acting as message carriers during intercellular communication. Here, we investigate protective effects of hBMSCs-derived EVs as a cell-free approach, on IL-1β stimulated chondrocytes from OA-patients. Methods: EVs were harvested from culture supernatant of hBMSCs by a sequential ultracentrifugation process. Western blot, scanning electron microscopy and nanoparticle tracking analysis were performed to characterize the purified particles. Intracellular incorporation of EVs, derived from PHK26 labeled hBMSCs, was tested by adding the labeled EVs to human OA chondrocytes (OA-CH), followed by fluorescence microscopy. Chondrocytes were pre-stimulated with IL-1β for 24 hours, followed by EVs treatment for 24 hours. Subsequently, proliferation, apoptosis, migration and relative expression level of anabolic and catabolic genes were determined. Furthermore, immunofluorescence microscopy and western blot were performed to evaluate the protein expression and phosphorylation levels of Erk1/2, PI3K/Akt, p38, TAK1 and NF-κB as components of pro-inflammatory signaling pathways in OA-CH. Results: EVs from hBMSCs (hBMSC-EVs) promote proliferation, reduce apoptosis of OA-CH and IL-1β-stimulated OA-CH and attenuate IL-1β-induced reduction of chondrocyte migration. Furthermore, hBMSC-EVs increase gene expression of PRG4, BCL2 and ACAN and decrease gene expression of MMP13, ALPL and IL1ß in OA-CH. Notably, COL2A1, SOX9, BCL2 ACAN and COMP gene expression levels were significantly increased in IL-1β+ EV groups compared with those IL-1β groups without EVs，whereas the gene expression levels of COLX, IL1B, MMP13 and ALPL were significantly decreased in IL-1β+ EV groups. In addition, phosphorylation status of Erk1/2, PI3K/Akt, p38, TAK1 and NF-κB signaling molecules, induced by IL-1β, is prevented by hBMSC- EVs. Conclusion: EVs derived from hBMSCs alleviated IL-1β-induced catabolic effects on OA-CH via promoting proliferation and migration and reducing apoptosis, probably via down regulation of IL-1ß activated pro-inflammatory Erk1/2, PI3K/Akt, p38, TAK1 and NF-κB signaling pathways. EVs released from BMSCs may be a promising cell-free intervention strategy in cartilage regenerative medicine avoiding adverse effects of cell-based regenerative approaches.